Digital Integration in Mosque Architecture: QRIS, Visitor Experience, and Cultural Heritage Preservation in Indonesia - Putra, Haris Maiza; Sofanudin, Aji; Ahyani, Hisam; Surbakti, Mhd Handika; Sonjaya, Adang; Martiningsih, Dwi; Ulum, Raudatul; Utaberta, Nangkula (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
This study investigates the integration of QRIS (Quick Response Code Indonesian Standard) in mosque architecture as both a digital innovation and a cultural intervention. Using qualitative case studies of three iconic mosques in Indonesia: Al-Jabbar (Bandung), Sheikh Zayed (Solo), and Hubbul Wathan (Lombok), the research analyzes how QRIS impacts visitor experience, philanthropic participation, and the preservation of architectural and cultural values. Drawing on theories of technology acceptance, vernacular architecture, and experiential learning, the study finds that QRIS can enrich mosque functionality without disrupting sacred spatial aesthetics. It also reveals the importance of inclusive design in ensuring that digital tools benefit diverse visitor groups. While emphasizing the transformative potential of QRIS, the study also notes challenges related to digital literacy and infrastructural disparities. This research contributes to current debates on digital heritage, smart religious spaces, and the adaptive use of technology in sustaining Islamic cultural identity.